Reaction of European bank and non-bank financial equities to physical climate risk: Evidence from quantile dependence and time-varying predictability - Olasehinde-Williams, Godwin; Akadiri, Seyi Saint (Edelweiss Applied Science and Technology, 2026)
This study analyses the pricing of physical climate risk in European financial equity markets by looking at the differentiated responses of banks and non-bank financial institutions. Daily data from December 2012 to December 2023 are used to study the predictive, causal, and distributional effects of physical climate risk on sectoral equity returns. The measurement of physical climate hazard is through a new text-based Physical Climate Risk Index, created from coverage in European financial media, which captures real-time investor attention to climate-related hazards. In terms of methodology, it employs an extensive econometric framework that integrates the wild-bootstrap likelihood ratio test for assessing return predictability, time-varying causal changes, and cross-quantilograms for studying asymmetric quantile-dependent dependencies at short, medium, and long-run horizons. The results provide strong evidence that physical climate risk has a statistically significant adverse predictive effect on both banking and non-bank financial equity returns, with more pronounced impacts for non-bank institutions. Time-varying causality intensifies in periods of heightened climate stress, particularly around major heat waves, droughts, and wildfire episodes within Europe. Further cross-quantilogram results reveal substantial asymmetries, stronger downside effects in the short run, and evidence of gradual market adaptation over longer horizons. Overall, the findings indicate that physical climate risk is a financially material, dynamically priced risk factor, underscoring the need for climate-aware sector-specific asset-pricing regulation and dynamic stress-testing frameworks.